Adhesive composition and protective film using the same
By using a binder composition containing two or more ionic liquids, the problem that the protective film in the prior art is difficult to meet various physical properties needs at the same time, and the performance improvement of the protective film in the efficient display panel manufacturing process is achieved.
Patent Information
- Application Number
- CN202111396823.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-23
- Filing Date
- 2021-11-23
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-11-23
AI Technical Summary
In the protective film used in the manufacturing process of display panels, it is difficult to meet the requirements of optical properties, wetting properties, adhesion, and low static electricity and low peeling charge voltages at the same time, and excessive use of antistatic agents will lead to opacity of the adhesive layer and surface contamination.
A binder composition containing two or more antistatic agents is used, and a polyurethane resin and a diisocyanate-based curing agent is combined with a protective film with excellent optical properties, wetting properties and adhesion, and the electrostatic phenomenon and peeling charge voltage are reduced during peeling.
The protective film used in the display panel manufacturing process is realized, with excellent optical properties, wetting properties and adhesion. The electrostatic phenomenon and peeling charge voltage are low during peeling, the surface pollution is low, and the physical properties such as adhesion are less changed over time.
Smart Images

Figure CN114525102B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive composition and a protective film using the same. Background Art
[0002] Various protective films are used in the manufacturing process of display panels.
[0003] Specifically, in the process of flipping the panel or attaching multiple chips to the back, a protective film is attached to absorb the impact applied to the front surface of the panel and prevent cracks or contamination of the conveyor belt. In this case, the physical properties required of the protective film vary depending on the type of panel.
[0004] For example, a display panel supported by glass or plastic material has a weak ability to withstand impact, and therefore, a protective film is required, that is, a film having a thickness that can withstand the impact applied during the process and a bonding function that can track the height difference generated by various printed patterns or shapes. The physical properties of the required protective film are as follows: First, it should have excellent adhesion (wettability) to the height difference (groove) on the surface of the adherend to which it is attached, and it needs to have a stable fit that will not curl from the surface over time; second, in the step of completing the process and removing the protective film, no foreign matter generated by the transfer of adhesive to the adherend or the scattering of adhesive should occur; and third, when the protective film is removed (peeled off) from the adherend, the peeling charge voltage should be low.
[0005] In order to meet such a demand, a method of forming a separate antistatic layer on the surface of the adhesive layer of the protective film has been studied, but this has the disadvantages of incurring additional time and cost and making the process complicated.
[0006] In this regard, the method of adding an antistatic agent inside the adhesive layer is mainly used. However, in order to meet the above requirements, a large amount of antistatic agent needs to be used. In this case, the antistatic agent is not completely decomposed in the adhesive layer, so that the adhesive layer may become opaque. Even if the adhesive layer is transparent, the excessive antistatic agent will move to the surface of the adhesive layer and cause stains on the surface of the adherend (panel or optical film), or there is a problem of changes in physical properties such as adhesion over time.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent document 1: Korean Publication No. 2002-0091198. Summary of the invention
[0010] The object of the present invention is to provide an adhesive composition and a protective film derived therefrom, that is, a protective film which can provide excellent physical properties such as optical properties, wettability and adhesive strength, has low static electricity and peeling charge voltage when peeled, has low surface contamination of the adherend, and has little change in the physical properties of the adhesive layer even after a long period of time.
[0011] The present invention provides an adhesive composition, which comprises a polyurethane resin, a diisocyanate curing agent and an antistatic agent, wherein the antistatic agent comprises two or more ionic liquids.
[0012] Furthermore, the present invention provides a protective film including a first base material layer and an adhesive layer in a laminated form, wherein the adhesive layer is derived from the adhesive composition.
[0013] The adhesive composition of the present invention contains an antistatic agent having two or more ionic liquids, thereby providing a protective film having excellent optical properties, wettability and adhesion when applied to a protective film, low electrostatic phenomena and peeling charge voltage when peeled, low surface contamination of the adherend, and little change in physical properties such as adhesion even after a long period of time. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 FIG. 4 is a schematic diagram of a protective film according to an embodiment of the present invention.
[0015] Figure 2 FIG. 4 is a schematic diagram of a protective film according to another embodiment of the present invention.
[0016] Description of Reference Numerals
[0017] 1: Protective film
[0018] 11: First substrate layer
[0019] 12: Adhesive layer
[0020] 13: Release layer
[0021] 14: Second substrate layer
[0022] 15: Second antistatic layer
[0023] 16: The first antistatic layer
[0024] 17: Release film DETAILED DESCRIPTION
[0025] The present invention is not limited to the contents disclosed below, and the present invention can be modified into various forms as long as the gist of the invention is not changed.
[0026] The terms used in the present invention are only used to describe specific embodiments and are not used to limit the present invention. Unless the context clearly indicates otherwise, a singular expression includes a plural expression.
[0027] In this specification, when it is described that a structural element is formed above or below another structural element, it includes a structural element that is directly formed above or below another structural element or is indirectly formed via the other structural element.
[0028] In addition, the top and bottom of each component are described with reference to the drawings. In the drawings, the size of each component may be exaggerated for the purpose of description and may be different from the actual size.
[0029] In this specification, unless otherwise specified, "including" means that other structural elements may also be included. In addition, unless otherwise specified, all numbers and expressions indicating the amounts of components, reaction conditions, etc. described in this specification should be understood to be modified by the term "about" in all cases.
[0030] Hereinafter, the present invention will be described in more detail.
[0031] Binder composition
[0032] An adhesive composition according to an embodiment of the present invention comprises a polyurethane resin, a diisocyanate curing agent and an antistatic agent, wherein the antistatic agent comprises two or more ionic liquids.
[0033] The ionic liquid is a salt that becomes liquid at room temperature and is composed of cations and anions. The ionic liquid has the following advantages, namely, low viscosity, excellent heat resistance and high ionic conductivity.
[0034] The adhesive composition of the present invention contains two or more ionic liquids as antistatic agents, thereby providing a protective film having excellent optical properties, wettability and adhesion, low peeling charge voltage, low surface contamination of the adherend, and little change in physical properties such as adhesion over time, even when a small amount of antistatic agent is used.
[0035] The two or more ionic liquids include a first ionic liquid and a second ionic liquid. The first ionic liquid includes a hydrophilic anion, and the second ionic liquid includes a hydrophobic anion.
[0036] The first ionic liquid may include an ionic liquid having excellent compatibility with the polyurethane resin and exhibiting polar hydrophilic anions. Furthermore, the second ionic liquid may include an ionic liquid having poor compatibility with the polyurethane resin and exhibiting non-polar hydrophobic anions. In this case, the "compatibility" may be determined by the polarity difference between the ionic liquid (the first ionic liquid or the second ionic liquid) and the polyurethane resin.
[0037] According to an example of the present invention, when the above two or more ionic liquids are mixed for use, the first ionic liquid having relatively excellent compatibility with the above polyurethane resin is used, and has appropriate miscibility with the polyurethane resin. When moving to the surface of the adhesive layer, the surface contamination of the adherend can be reduced. Since the second ionic liquid having relatively poor compatibility with the above polyurethane resin is used, even if a small amount of antistatic agent is used, the stripping charge voltage can be effectively reduced. In particular, when the above two or more ionic liquids are appropriately combined for use, even if a small amount of antistatic agent is used, the physical property changes of the adhesive force, etc. can be minimized over time, and the effect of reducing the stripping charge voltage can be maximized.
[0038] The hydrophilic anion may include a chloride anion (Cl - ), bromide anion (Br - ), iodide anion (I - ), nitrate anion (NO3 - ) and acetate anion (CH3CO2 - ) is one or more of the group consisting of. Specifically, the hydrophilic anion may include a bromine anion (Br - ), iodide anion (I - ), nitrate anion (NO3 - ) and acetate anion (CH3CO2 - ) is one or more of the group consisting of.
[0039] The hydrophobic anion may include an anion selected from the group consisting of hexafluorophosphate anion (PF6 - ), tetrafluoroborate anion (BF4 - ), bis((trifluoromethyl)sulfonyl)imide anion (TFSI - ) and trifluoromethanesulfonate anion (TF - ) is one or more of the group consisting of. Specifically, the hydrophobic anion may include an anion selected from hexafluorophosphate anion (PF6 - ), tetrafluoroborate anion (BF4 -The first ionic liquid and the second ionic liquid may each contain one or more cations selected from the group consisting of alkyl imidazolium cations, dialkyl imidazolium cations, trialkyl imidazolium cations, tetraalkyl imidazolium cations, alkyl pyridinium cations, dialkyl pyridinium cations, dialkyl piperidinium cations, alkyl pyrimidinium cations, alkyl pyrazolium cations, sulfonium cations, alkyl pyrrolidinium cations, alkyl ammonium cations, and alkyl phosphonium cations.
[0040] Specifically, the cations contained in the first ionic liquid and the second ionic liquid may include one or more selected from the group consisting of alkylimidazolium cations, dialkylimidazolium cations, and alkylammonium cations.
[0041] The cation is selected regardless of the types of the hydrophilic anion and the hydrophobic anion, and can be combined with the hydrophilic anion and the hydrophobic anion to constitute the first ionic liquid and the second ionic liquid.
[0042] For example, the first ionic liquid may include alkylammonium cations and nitrate anions (NO3 - Alternatively, the first ionic liquid may include an alkylammonium cation and an acetate anion (CH3CO2 - Alternatively, the first ionic liquid may include an alkyl imidazolium cation and an acetate anion (CH3CO2 - Alternatively, the first ionic liquid may include an alkyl imidazolium cation and a nitrate anion (NO3 - ).
[0043] The second ionic liquid may include an alkyl imidazolium cation and a hexafluorophosphate anion (PF6 - Alternatively, the second ionic liquid may include a dialkyl imidazolium cation and a hexafluorophosphate anion (PF6 - Alternatively, the second ionic liquid may include an alkylammonium cation and a hexafluorophosphate anion (PF6 - Alternatively, the second ionic liquid may include an alkyl imidazolium cation and a tetrafluoroborate anion (BF4 - ).
[0044] According to an example of the present invention, the first ionic liquid and / or the second ionic liquid may not contain metal ions. When the first ionic liquid and / or the second ionic liquid contain metal ions, for example, metal cations, the metal cations that are not combined with the polyurethane resin may combine with anions and cause crystallization, and the crystallized metal salt will cause scattering to blur the coating or increase the surface contamination of the adherend.
[0045] On the other hand, the contents of the first ionic liquid and the second ionic liquid are important in improving the physical properties of the adhesive composition and the protective film using the same.
[0046] According to an example of the present invention, the weight ratio of the first ionic liquid to the second ionic liquid may be 1:0.1 to 1:2.0. Specifically, the weight ratio of the first ionic liquid to the second ionic liquid may be 1:0.6 to 1:1.2, 1:0.6 to 1:1.0, or 1:0.8 to 1:1.0. When within the above range, even with a small amount of antistatic agent, over time, the change in physical properties such as adhesion can be minimized, and the stripping charge voltage reduction effect can be maximized.
[0047] Furthermore, the antistatic agent comprising the first ionic liquid and the second ionic liquid may be included in an amount of 0.2 to 6 parts by weight, 0.4 to 5 parts by weight, 0.4 to 4 parts by weight, 0.4 to 3 parts by weight, or 1 to 3 parts by weight relative to 100 parts by weight of the polyurethane resin. When the content of the antistatic agent is greater than the above range, the haze will increase, thereby limiting the use as a protective film requiring transparency.
[0048] The first ionic liquid may be present in an amount of 0.1 to 3 parts by weight, 0.2 to 2 parts by weight, 0.2 to 1.8 parts by weight, 0.2 to 1.5 parts by weight, or 0.5 to 1.5 parts by weight relative to 100 parts by weight of the polyurethane resin. When within the above range, the first ionic liquid has appropriate miscibility with the polyurethane resin and can reduce the surface contamination of the adherend when it moves to the surface of the adhesive layer.
[0049] The second ionic liquid may be included in an amount of 0.1 to 3 parts by weight, 0.2 to 2 parts by weight, 0.2 to 1.8 parts by weight, 0.2 to 1.5 parts by weight, or 0.5 to 1.5 parts by weight relative to 100 parts by weight of the polyurethane resin. When within the above range, even with a small amount of antistatic agent, the stripping charge voltage can be effectively reduced.
[0050] On the other hand, the polyurethane resin can be produced by reacting a polyol with an isocyanate compound.
[0051] The isocyanate compound used in the preparation of the polyurethane resin may be one selected from the group consisting of aromatic diisocyanates, aliphatic diisocyanates, alicyclic diisocyanates, and combinations thereof.
[0052] For example, the isocyanate compound may include one selected from the group consisting of 2,4-toluenediisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), naphthalene-1,5-diisocyanate, p-phenylenediisocyanate, tolidine diisocyanate, 4,4'-diphenyl methane diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, and combinations thereof.
[0053] The polyol is a compound containing at least two hydroxyl groups (-OH) per molecule, and may include, for example, one selected from the group consisting of polyether polyol, polyester polyol, polycarbonate polyol, acryl polyol, and combinations thereof.
[0054] For example, the polyol may include one selected from the group consisting of polytetramethylene ether glycol, polypropylene ether glycol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 2-methyl-1,3-propylene glycol, 1,4-butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, tripropylene glycol, and combinations thereof.
[0055] The weight average molecular weight of the polyol may be about 100 g / mol to 3000 g / mol. For example, the weight average molecular weight of the polyol may be about 100 g / mol to 3000 g / mol, for example, about 100 g / mol to 2000 g / mol, for example, about 100 g / mol to 1800 g / mol.
[0056] In one example, the polyol may include a low molecular weight polyol having a weight average molecular weight of about 100 g / mol or more and less than about 300 g / mol or more and a high molecular weight polyol having a weight average molecular weight of about 300 g / mol or more and about 1800 g / mol or less.
[0057] The weight average molecular weight (Mw) of the polyurethane resin may be about 500 g / mol to 3000 g / mol, for example, about 1000 g / mol to 2000 g / mol, for example, about 1000 g / mol to 1500 g / mol.
[0058] On the other hand, the diisocyanate curing agent may be an aliphatic isocyanate compound, an alicyclic isocyanate compound, an aromatic isocyanate compound, or the like having two or more functional groups.
[0059] Specifically, the diisocyanate curing agent is toluene diisocyanate, methylene diphenyl diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate trimer, toluene diisocyanate trimer, isophorone diisocyanate trimer or a mixture thereof. More specifically, it can be hexamethylene diisocyanate trimer or isophorone diisocyanate trimer.
[0060] Hexamethylene diisocyanate trimer is more advantageous in ensuring the flexibility of the adhesive layer, and isophorone diisocyanate trimer has a slow reaction rate but is advantageous in forming a strong film.
[0061] The diisocyanate curing agent may be included in an amount of 1 to 10 parts by weight, 3 to 10 parts by weight, 3 to 8 parts by weight, or 3 to 5 parts by weight, relative to 100 parts by weight of the polyurethane resin.
[0062] On the other hand, the adhesive composition of another embodiment of the present invention may include a polyurethane resin, a diisocyanate curing agent and an antistatic agent, and may further include a slip agent and a catalyst as required.
[0063] The slip agent imparts lubricating properties (slip properties) to the adhesive composition.
[0064] The slip agent can be obtained by combining at least one selected from the group consisting of organic modified polydimethylsiloxane compounds, fluorine modified polyacrylate compounds, and perfluoropolyether (PFPE) compounds.
[0065] The slip agent may be a polydimethylsiloxane compound containing a hydroxyl functional group. The weight average molecular weight of the polydimethylsiloxane compound containing a hydroxyl functional group may be 1000 g / mol to 50000 g / mol or 10000 g / mol to 50000 g / mol.
[0066] The polydimethylsiloxane compound containing the hydroxyl functional group can be combined with the acrylic copolymer containing an addition bond of a vinyl monomer to migrate to the surface of the adherend to suppress the reduction of the surface properties of the adherend.
[0067] The slip agent may be included in an amount of 0.1 to 10 parts by weight, 0.1 to 7 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 0.1 to 1.5 parts by weight relative to 100 parts by weight of the polyurethane resin. When within the above range, an adhesive layer having excellent adhesive force can be provided.
[0068] The catalyst acts as a promoter to promote the reaction. The catalyst may include a tin catalyst, specifically, may include one or more selected from the group consisting of stannous octoate, dibutyltin dilaurate, and dioctyltin dilaurate.
[0069] The catalyst may be included in an amount of 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, 0.1 to 2.5 parts by weight, or 0.2 to 2 parts by weight relative to 100 parts by weight of the polyurethane resin. When within the above range, an adhesive layer having excellent adhesive force can be provided.
[0070] Furthermore, the above-mentioned adhesive composition may further contain various additives which are generally used as long as the objective effect of the present invention is not hindered.
[0071] Protective film
[0072] Another embodiment of the present invention provides a protective film comprising an adhesive layer derived from the above adhesive composition. Figure 1 The protective film 1 of the present invention includes a first substrate layer 11 and an adhesive layer 12 derived from the adhesive composition in a laminated form. For example, the protective film 1 includes a first substrate layer 11 and an adhesive layer 12 formed on the first substrate layer 11 and derived from the adhesive composition.
[0073] Hereinafter, each layer of the protective film will be described in detail.
[0074] First substrate layer
[0075] The protective film of the example of the present invention may include a base layer of a generally used protective film, for example, may include a plastic film as a first base layer.
[0076] The first substrate layer may be a plastic film of polyethylene (PE), polypropylene (PP), polycarbonate (PC), polyimide (PI), polyethylene terephthalate (PET), etc., and specifically, may be polyethylene terephthalate. Polyethylene terephthalate is excellent in durability, mechanical strength, and transparency.
[0077] The first substrate layer may have a thickness of 188 μm or less, 125 μm or less, 100 μm or less, 30 μm to 188 μm, 30 μm to 125 μm, 38 μm to 100 μm, or 50 μm to 100 μm. Considering handling and flexibility, the first substrate layer may have a thickness of 38 μm to 100 μm.
[0078] The first substrate layer may have 10 4 Ω / □ to 10 12 Ω / □、10 4 Ω / □ to 10 11 Ω / □ or 10 4 Ω / □ to 10 10 Surface resistance of Ω / □.
[0079] For example, the first substrate layer may have a thickness of 38 μm to 100 μm and a 4 Ω / □ to 10 12 Surface resistance of Ω / □.
[0080] Adhesive layer
[0081] The protective film of the present example includes an adhesive layer derived from the above adhesive composition.
[0082] The details of the above-mentioned adhesive composition are as described above.
[0083] The adhesive layer may be formed by curing the adhesive composition as a coating on one side of the first substrate layer. Specifically, the adhesive layer may be formed by coating the adhesive composition on the first substrate layer, and then heat drying and curing the adhesive composition at a temperature of 100° C. to 130° C. or 110° C. to 120° C. for 1 minute to 5 minutes or 1 minute to 3 minutes.
[0084] The thickness of the adhesive layer may be 15 to 100 μm, 15 to 95 μm, 15 to 90 μm, 15 to 85 μm or 15 to 75 μm. When within the above range, the display panel can be effectively protected from physical impacts such as pressing and puncturing, thereby preventing scratches.
[0085] The above-mentioned adhesive layer may have 10 8 Ω / □ to 10 12 Ω / □、10 8 Ω / □ to 10 11 Ω / □ or 10 8 Ω / □ to 10 10 Surface resistance of Ω / □.
[0086] For example, the adhesive layer may have a thickness of 15 μm to 100 μm and a 8 Ω / □ to 10 12 Surface resistance of Ω / □.
[0087] On the other hand, in the protective film of the example of the present invention, for the above-mentioned adhesive layer, the peeling charging voltage measured at a peeling angle of 180° and a peeling speed of 15 m / min under the conditions of 25°C and 50% relative humidity (RH) can be 200 V or less, 180 V or less, 160 V or less, 150 V or less, 140 V or less, 130 V or less, 120 V or less, 110 V or less, 100 V or less, or 90 V or less. The above-mentioned peeling charging voltage can be 10 V or more, 15 V or more, 20 V or more, 22 V or more, 25 V or more, or 30 V or more.
[0088] The peeling charge voltage refers to the amount (voltage) of static electricity generated on the surface of an adherend when the protective film is peeled off after being attached to the adherend.
[0089] According to an example of the present invention, an antistatic agent containing two or more ionic liquids is used, whereby a low peeling charge voltage of 200 V or less can be easily achieved even when a small amount of the antistatic agent is used.
[0090] Furthermore, in the protective film of the present invention, the change in the physical properties of the adhesive layer over time, for example, the change in the adhesive force change rate or the residual adhesive force reduction rate, etc., is small.
[0091] For example, the adhesive force change rate (A (%)) expressed by the following formula 1 measured for the adhesive layer may be 50% or less.
[0092] Formula 1:
[0093] In the above formula 1, A1 is the adhesive strength measured by peeling off the adhesive layer after attaching it to the adherend for 1 hour at a temperature of 25°C, and A2 is the adhesive strength measured by peeling off the adhesive layer after attaching it to the adherend for 30 days at a temperature of 25°C.
[0094] Specifically, the adhesive force change rate (A(%)) measured for the above-mentioned adhesive layer can be less than 45%, less than 40%, less than 35%, less than 33% or less than 30%. When it is in the above range, the adhesive force change rate will not increase after being attached to the adherend for a long time, so that the protective film can be peeled off without deformation or damage to the adherend. In the case where the adhesive force change rate (A(%)) measured for the above-mentioned adhesive layer is greater than the above range, when peeling off the protective film, deformation or damage such as bending of the adherend may occur.
[0095] The above-mentioned A1 can be 0.1gf / inch to 10gf / inch, 0.1gf / inch to 7gf / inch, 0.1gf / inch to 5gf / inch, 0.1gf / inch to 3gf / inch, 0.1gf / inch to 2.5gf / inch, 0.1 to 2.2gf / inch, 0.1gf / inch to 2gf / inch, 0.1gf / inch to 1.8gf / inch or 0.3gf / inch to 1.8gf / inch.
[0096] The above-mentioned A2 can be 1gf / inch to 15gf / inch, 1gf / inch to 8gf / inch, 1gf / inch to 7gf / inch, 1gf / inch to 5gf / inch, 1gf / inch to 4gf / inch, 1.2gf / inch to 3gf / inch, 1.2gf / inch to 2.3gf / inch or 1.5gf / inch to 2.2gf / inch.
[0097] Furthermore, the adhesive layer may have a residual adhesive force retention rate (RA (%)) represented by the following Formula 2 of 80% or more.
[0098] Formula 2:
[0099] In the above 2, N1 is the adhesive strength of the Nitto 31B tape to the adherend, and N2 is the adhesive strength of the Nitto 31B tape to the adherend measured at 60°C and 90% relative humidity (RH) after the adhesive layer was attached to the adherend for 120 hours and then peeled off.
[0100] Specifically, for the above-mentioned adhesive layer, the residual adhesive force retention rate (RA (%)) can be 80% or more, 82% or more, 83% or more, 85% or more, 87% or more, 88% or more, 90% or more, or 92% or more.
[0101] The higher the residual adhesive force retention rate of the adhesive layer is, the less stains or residues will remain on the surface of the adherend, and the lower the degree of contamination such as whitening will be.
[0102] Furthermore, the protective film of the example of the present invention has excellent optical characteristics of haze and transmittance.
[0103] Specifically, the haze of the protective film may be 5% or less, 4% or less, or 3% or less.
[0104] The transmittance of the protective film may be 80% or more, 85% or more, 86% or more, 88% or more, or 90% or more.
[0105] For example, the protective film may have a haze of 5% or less and a transmittance of 80% or more. Specifically, the protective film may have a haze of 4% or less and a transmittance of 85% or more. Alternatively, the protective film may have a haze of 3% or less and a transmittance of 86% or more.
[0106] Furthermore, according to an example of the present invention, when an adhesive composition containing two or more particle liquids is used as an antistatic agent, even if an excessive amount of the antistatic agent is used, excellent optical properties can be maintained, and a low peeling charge voltage and adhesion change rate as well as improved surface contamination results can be provided.
[0107] Release film
[0108] The protective film of the embodiment of the present invention may further include a release film formed on the other side of the adhesive layer.
[0109] Reference Figure 2 The protective film 1 may include a first substrate layer 11 , an adhesive layer 12 , and a release film 17 in a sequentially stacked state.
[0110] Specifically, the release film 17 may include a second substrate layer 14 and a release layer 13 in a sequentially stacked state.
[0111] For example, the release film 17 may include a second substrate layer 14 and a release layer 13 formed on one side of the second substrate layer 14. In this case, the adhesive layer 12 and the release layer 13 may be in contact with each other.
[0112] In addition, the protective film 1 may further include a first antistatic layer 16 formed on the other side of the first substrate layer 11 , and the release film 17 may further include a second antistatic layer 15 formed on the other side of the second substrate layer 14 .
[0113] Specifically, the second base layer may include the same components as those of the first base layer, and may have the same physical properties as those of the first base layer.
[0114] The release layer may include a silicone release layer, and a polysiloxane polymer having a group reactive to a group containing a Si-H bond in the molecule may be used. The group reactive to a group containing a Si-H bond may include an alkenyl group, for example, one or more selected from the group consisting of a vinyl group and a hexenyl group.
[0115] The release layer may have a thickness of 0.1 μm to 1 μm, preferably 0.1 μm to 0.3 μm. If the release layer has a thickness less than 0.1 μm, it is difficult to exhibit the characteristics of a release film, and if it has a thickness greater than 1 μm, adhesion may occur.
[0116] The release layer may have a peeling force of 5 gf / inch to 70 gf / inch or less based on Tesa 7475. When it is within the above range, it may not be separated from the adhesive layer alone in the punching process for sheeting, and the release film can be easily peeled off in the lamination process.
[0117] The protective film of the present embodiment can be prepared by applying the adhesive composition on one side of the first substrate layer and heat drying to form an adhesive layer, and then laminating a release film, more precisely, the release layer of the release film, on one side of the adhesive layer.
[0118] As the coating method, for example, gravure roll coating, Meyer bar coating, doctor blade coating, curtain coating, comma coating, slot die coating, etc. can be used. Considering the thickness of the adhesive layer, preferably, comma coating and slot die coating can be used.
[0119] On the other hand, the first antistatic layer and the second antistatic layer can be formed by coating a conventionally known material such as a conductive polymer (eg, poly(3,4-ethylenedioxythiophene) (PEDOT)) or an ionic liquid on the other surface of the base layer.
[0120] The first antistatic layer and the second antistatic layer may have 10 12 Ω / □ or less, 10 10 Ω / □ or less, 10 4 Ω / □ to 10 12 Ω / □ or 10 4 Ω / □ to 10 10 When the surface resistance is within the above range, it is more advantageous in terms of the foreign matter adsorption inhibition effect.
[0121] The protective film of the example of the present invention has excellent optical properties, wettability and adhesion. When peeled off, the static electricity phenomenon and the peeling charge voltage are low, the surface contamination of the adherend is low, and even after a long time, the physical properties of the adhesive layer change little. Therefore, it can be effectively used as a protective film in the display panel preparation process.
[0122] The present invention will be described in more detail below by way of examples. The following examples are only used to illustrate the present invention, and the scope of the present invention is not limited thereto.
[0123] Example
[0124] Example 1
[0125] <Preparation of Adhesive Composition>
[0126] 100 parts by weight of a polyurethane resin copolymerized with a polyol and an isocyanate (SH-109, Toyo Ink), 4 parts by weight of a hexamethylene diisocyanate trimer (T-501B, Toyo Ink) as a diisocyanate curing agent, 1 part by weight of a slip agent (BYK377, BYK), 0.5 parts by weight of a tin catalyst (BXX3778-10, Toyo Ink), 0.5 parts by weight of an alkylammonium cation ( M3BN + ) and NO3 - The first ionic liquid and 0.5 parts by weight of an alkyl imidazolium cation ( BMI + ) and PF6 - The binder composition is prepared by using a second ionic liquid.
[0127] <Preparation of protective film>
[0128] A polyethylene terephthalate substrate layer (first substrate layer) with a thickness of 75 μm and a release film (RF02N, SKC hi-tech & marketing) with a thickness of 25 μm were prepared, and the adhesive composition prepared in the above-mentioned Example 1 was coated on one side of the substrate layer in such a way that the adhesive layer was located between the above-mentioned substrate layer and the release film, and heat dried at a temperature of 120°C for 3 minutes to prepare a protective film including a 75 μm thick adhesive layer.
[0129] Example 2 and Example 3
[0130] As shown in Table 1 below, an adhesive composition and a protective film were prepared by the same method as in Example 1, except that the contents of the first ionic liquid and the second ionic liquid as antistatic agents were adjusted differently.
[0131] Comparative Examples 1 to 3
[0132] As shown in Table 1 below, an adhesive composition and a protective film were prepared by the same method as in Example 1, except that LiTFSi was used alone as an antistatic agent and its content was adjusted differently.
[0133] Comparative Examples 4 and 5
[0134] As shown in Table 1 below, in addition to using alkyl imidazolium cation (BMI) alone as an antistatic agent + ) and PF6 - The adhesive composition and the protective film were prepared by the same method as in Example 1, except that the content of the second ionic liquid was adjusted differently.
[0135] Comparative Examples 6 and 7
[0136] As shown in Table 1 below, in addition to using alkylammonium cations (M3BN + ) and NO3 - The adhesive composition and the protective film were prepared by the same method as in Example 1, except that the content of the first ionic liquid was adjusted differently.
[0137] Test example
[0138] Test Example 1: Adhesion
[0139] Adhesion force change rate
[0140] After removing the release film from the protective film prepared in the embodiment and the comparative example, the adhesive force (A1) measured by peeling off the adhesive layer after being attached to the adherend for 1 hour at a temperature of 25°C and the adhesive force (A2) measured by peeling off the adhesive layer after being attached to the adherend for 30 days at a temperature of 25°C were respectively measured, and then substituted into the following formula 1 to obtain the adhesive force change rate.
[0141] Formula 1:
[0142] Specifically, A1 is the initial adhesive force measured by peeling off the adhesive layer after it is attached to the adherend for 1 hour at a temperature of 25°C. After the protective film prepared in Example and Comparative Example 1 is cut into a width of 1 inch and the release film is removed, it is attached to glass at a temperature of 25°C for 1 hour, and then peeled off at an angle of 180° at a peeling speed of 0.3 m / min and measured.
[0143] The above A2 is the adhesive strength measured by peeling off the adhesive layer after it is attached to the adherend for 30 days at a temperature of 25°C. The protective film prepared in Example and Comparative Example 1 was cut into a width of 1 inch and the release film was removed. The protective film was attached to glass at a temperature of 25°C for 30 days and then peeled off at an angle of 180° at a peeling speed of 0.3 m / min and measured.
[0144] Residual Adhesion Retention Rate (RA (%))
[0145] The adhesive strength (N1) of the Nitto 31B tape to the adherend was measured.
[0146] In addition, the adhesive strength (N2) to the adherend of Nitto 31B tape was measured after the release film was removed from the protective film prepared in the examples and comparative examples, and the adhesive layer was attached to the adherend for 120 hours under the conditions of 60°C and 90% relative humidity (RH), and then peeled off and measured. The above N1 and N2 were respectively substituted into the following formula 2 to obtain the residual adhesive strength retention rate (RA (%)).
[0147] Formula 2:
[0148] Specifically, N1 is the adhesive strength of the Nitto 31B tape measured by attaching the Nitto 31B tape cut into 1 inch pieces to glass, leaving it at 25° C. for 1 hour, and then peeling it off at an angle of 180° at a peeling speed of 0.3 m / min.
[0149] The above N2 is a glass protective film in which the adhesive layer is attached to the glass for 120 hours at 60°C and 90% relative humidity (RH). In its position, a Nitto 31B tape cut into 1 inch pieces is attached to the glass. After being placed at a temperature of 25°C for 1 hour, the Nitto 31B tape is peeled off at an angle of 180° at a peeling speed of 0.3m / min and the adhesive strength of the Nitto 31B tape is measured.
[0150] Test Example 2: Surface contamination
[0151] After removing the release film from the protective film prepared in the examples and comparative examples, the protective film was attached to glass and left at 60° C. and 90% RH for 120 hours. After that, the protective film was removed and the degree of contamination on the glass surface was visually checked under 3-wavelength illumination.
[0152] If there was no stain or residue left, it was evaluated as PASS. If there was visible stain or whitening phenomenon or residue of the adhesive layer, it was evaluated as NG.
[0153] Test Example 3: Stripping Voltage
[0154] The protective films prepared in the examples and comparative examples were cut into pieces with a width of 10 cm and a length of 25 cm, and after removing the release film, the films were left attached to the glass at 25°C for 1 hour, and then peeled off at an angle of 180° at a peeling speed of 15 m / min at 25°C and a relative humidity (RH) of 50%, and the maximum voltage on the glass surface was measured at a distance of 2 cm.
[0155] Test Example 4: Haze and Transmittance
[0156] The haze and transmittance of the protective films prepared in Examples and Comparative Examples were measured using a haze meter NDH-5000W manufactured by Japan Tensyoku Co., Ltd. after removing the release films.
[0157] Test Example 5: Surface resistance
[0158] The surface resistance of the adhesive layer surface of the protective film prepared in the examples and comparative examples was measured at 22° C. and 50% relative humidity (RH) using a high ohmmeter (Model No. MCT-HT450) manufactured by Mistubishi Corporation.
[0159] Table 1
[0160]
[0161]
[0162]
[0163] Observing the experimental results in Table 1 above, the protective films of Examples 1 to 3 using an adhesive composition containing two or more ionic liquids as an antistatic agent exhibit the same level of optical properties as compared to the protective films of the comparative examples using one metal salt or ionic liquid, exhibit low peeling charge voltage and adhesion change rate, and exhibit excellent residual adhesion retention and improved surface contamination.
[0164] Specifically, in the case of stripping charging voltage, the protective films of Examples 1 to 3 are 30V to 140V, which is significantly reduced compared with the protective films of Comparative Examples 1 to 4, Comparative Examples 6 and Comparative Examples 7 of 205V to 490V. In the case of the adhesive force change rate of the adhesive layer, the protective films of Examples 1 to 3 are 20% to 33.3%, which is significantly reduced compared with the protective films of the comparative examples. In particular, the adhesive force change rate is significantly increased to 92.9% compared with the protective film of Comparative Example 3 using 5 parts by weight of LiTFSi.
[0165] On the other hand, in the case of the residual adhesion retention rate of Nitto 31B tape, the protective films of Examples 1 to 3 were 82.9% to 93.5%, which was significantly improved compared to the protective films of the comparative examples. In the case of surface contamination, the protective films of Examples 1 to 3 did not have any residual stains or residues, nor did they experience any whitening phenomenon.
[0166] Furthermore, if the protective films of Example 3 and Comparative Examples 2, 3, 5 and 7, which use an excess of 3 parts by weight or more of antistatic agent, are compared, the protective film of Example 3 will maintain excellent optical properties even if an excessive amount of antistatic agent is used, and will also exhibit low peeling charge voltage and adhesion change rate, excellent residual adhesion retention rate and improved surface contamination results compared to the protective films of the above-mentioned comparative examples.
[0167] Therefore, it can be confirmed from the above results that according to the examples of the present invention, compared with the protective film of the comparative example prepared using the antistatic agent alone, the protective film of the embodiment prepared using two different ionic liquids can maintain excellent optical properties, and show improved effects in adhesion, peeling charge voltage, physical property changes over time, and contamination results on the glass surface.
Claims
1. A binder composition, characterized in that: It comprises a polyurethane resin, a diisocyanate curing agent and an antistatic agent, wherein the antistatic agent comprises two or more ionic liquids; The two or more ionic liquids include a first ionic liquid and a second ionic liquid, the first ionic liquid includes a hydrophilic anion, and the second ionic liquid includes a hydrophobic anion. The hydrophilic anion comprises a chloride anion Cl - , bromide anion Br - , iodide anion I - 、Nitrate anion NO3 - and acetate anion CH3CO2 - One or more of the group consisting of The hydrophobic anion comprises a hexafluorophosphate anion PF6 - 、Tetrafluoroborate anion BF4 - , bis((trifluoromethyl)sulfonyl)imide anion TFSI - and trifluoromethanesulfonate anion TF - One or more of the group consisting of; The first ionic liquid and the second ionic liquid each contain one or more cations selected from the group consisting of alkylimidazolium cations, dialkylimidazolium cations, trialkylimidazolium cations, tetraalkylimidazolium cations, alkylpyridinium cations, dialkylpyridinium cations, dialkylpiperidinium cations, alkylpyrimidinium cations, alkylpyrazolium cations, sulfonium cations, alkylpyrrolidinium cations, alkylammonium cations, and alkylphosphonium cations; The weight ratio of the first ionic liquid to the second ionic liquid is 1:0.1 to 1:2.0; The first ionic liquid is contained in an amount of 0.1 to 3 parts by weight relative to 100 parts by weight of the polyurethane resin; and the second ionic liquid is contained in an amount of 0.1 to 3 parts by weight.
2. The adhesive composition according to claim 1, characterized in that The content of the diisocyanate curing agent and the antistatic agent is 1 to 10 parts by weight and 0.2 to 6 parts by weight, respectively, relative to 100 parts by weight of the polyurethane resin.
3. The adhesive composition according to claim 1, characterized in that The adhesive composition further comprises 0.1 to 10 parts by weight of a slip agent and 0.1 to 5 parts by weight of a catalyst, relative to 100 parts by weight of the polyurethane resin.
4. A protective film, characterized in that: The adhesive composition comprises a first base material layer and an adhesive layer in a laminated form, wherein the adhesive layer is derived from the adhesive composition according to claim 1 .
5. The protective film according to claim 4, characterized in that: The adhesive layer has a peeling charge voltage of 200 V or less when measured at a peeling angle of 180° and a peeling speed of 15 m / min under the conditions of 25° C. and a relative humidity RH of 50%.
6. The protective film according to claim 4, characterized in that: The adhesive force change rate A% expressed by the following formula 1 measured for the adhesive layer is 50% or less, and the residual adhesive force retention rate RA% expressed by the following formula 2 is 80% or more. Formula 1: In the above formula 1, A1 is the adhesive strength measured by attaching the adhesive layer to the adherend for 1 hour and then peeling it off at a temperature of 25°C. A2 is the adhesive strength measured by attaching the adhesive layer to the adherend 30 days later and then peeling it off at a temperature of 25°C. Formula 2: In the above 2, N1 is the adhesion of Nitto 31B tape to the adherend. N2 is the adhesive strength of the Nitto 31B tape to the adherend measured under the conditions of 60° C. and 90% relative humidity RH, after the adhesive layer was attached to the adherend for 120 hours and then peeled off.
7. The protective film according to claim 4, characterized in that: The adhesive layer has a thickness of 15 μm to 100 μm and a 8 Ω / □ to 10 12 Surface resistance of Ω / □, The first substrate layer has a thickness of 38 μm to 100 μm and a 4 Ω / □ to 10 12 Surface resistance of Ω / □.
8. The protective film according to claim 4, characterized in that: The protective film further comprises a release film formed on the other side of the adhesive layer. The release film includes a second substrate layer and a release layer in a laminated form, and the adhesive layer is in contact with the release layer.
9. The protective film according to claim 8, characterized in that: The protective film further includes a first antistatic layer formed on the other side of the first substrate layer. The release film further includes a second antistatic layer formed on the other side of the second substrate layer.
Citation Information
Patent Citations
Adhesive, adhesive sheet, and laminate
JP2019173024A